Formation of a set of indicators to assess the effectiveness of functioning of urban public passenger transport - Koleber, Yuliya А.; Mochalin, Sergey М. (International journal of advanced studies, 2025)
Background. One of the important components of the assessment of the public urban passenger transport system is the formation of an initial set of indicators (criteria). To date there is no single set of indicators for the functioning of urban passenger transportation. The author of each study chooses the composition of indicators (often also a single indicator) that he considers the most significant and sufficient in order to quantify the system. As a result, only a part of the transport process is evaluated, while many indicators that could fully reflect the state of the system are neglected. This is due, in particular, to the fact that the formation of a large set of initial data greatly complicates the evaluation procedure. Most often, the indicators that the passenger is interested in improving are selected for evaluation. However, in the system of urban land passenger transport for general use, there are also other participants such as the customer of transport services and the carrier, whose interests should also be taken into account in order to form adequate estimates and develop rational corrective solutions. The goal is to form and substantiate a set of indicators (criteria) for evaluating the public urban land passenger transport system that would reflect the interests of each of the participants in the transport process. Methodology. The method of analysis and the method of data systematization are used. Results. The evaluation indicators of the urban land passenger transport system for general use, proposed by scientists, as well as regulated by normative documents, are investigated. Based on the results of the study, a fairly complete set of indicators was formed and grouped into enlarged blocks for each of the system participants: for the passenger, for the carrier, for the customer of transport services. The requirements for the initial set of indicators for evaluating the urban land passenger transport system are formulated. The scope of the results. The results obtained can be used by scientists, as well as experts in the field of transport, to assess the functioning of urban passenger transportation. Conclusions. The selected indicators take into account all aspects of the qualitative component of the transport process: comfort, safety, contact, reliability, accessibility, information service and efficiency. The generated list can be supplemented or adjusted depending on the objectives of the assessment subjects or the opinion of experts.